Panitia Seminar Nasional Kimia 2023 - Widodo, Nanang Tri (PROSIDING SEMINAR KIMIA, 2023)
PengarahDr. Dra. Hj. Ratna Kusuma, M.SiProf. Dr. Bohari, M.Si Penanggung JawabDr. Dadan Hamdani, M.SiDr. Yanti Puspita Sari, M.SiDr. Rudi Kartika, M.Si Ketua Ritbey Ruga, M.P., Ph.D SekretarisRita Hairani, M.Sc Siti Maisarah, S.Pd BendaharaDr. Noor Hindryawati. M.Si AnggotaDr. Saibun Sitorus, M.SiDr. Subur P. Pasaribu, M.Si Dr. Chairul Saleh, M.SiAlimuddin, M.SiRitson Purba, M.SiHusna Syaima, M.SiIrfan Ashari Hiyahara, M.SiMoh. Saiful Arif, S.Pd. M.SiDjihan Ryn Pratiwi, M.SiVeliyana Londong A, M.Si Ika Yekti Lianasari, M.SiDr. Winni Astuti, M.SiNanang Tri Widodo, M.SiAhmad Maulana, S.SiMuhammad Fadlianur, S.SiArbain Wawinca, SERahman Raya, S.PdManja’a Khasanah,S.Si